Electrochemical, HR-XPS and SERS study of the self-assembly of biphenyl 4,4′-dithiol on Au(111) from solution phase - Euti, Esteban (2014)
We report a comparative study of 4,4′-biphenyldithiol adlayers grown on Au(111) substrates in solution phase by different methods. Layers prepared by immersion in solutions of ethanol and n-hexane, with and without the use of a disulfide reducing agent (tris-carboxyethyl phosphine, TCEP),were characterized by electroreductive desorption, impedance spectroscopy, redox activity, high-resolution photoemission spectroscopy, and surfaceenhanced Raman spectroscopy. It is shown that the simple immersion in an ethanolic solution leads to the formation of, at least, a bilayerwith a high number of S\S bonds. The use of n-hexane as solvent produces a drastic reduction of these undesired bonds, and a similar result is obtained if the substrates prepared in the ethanolic solution are then washed with TCEP. The best results were obtained when the reducing agent was added into the ethanol solution, in which case all the characterizations were coincident in the formation of a single layer of standing-up molecules free of S\S bonds. The charge of the desorption peak and the relative intensity of the S2p and Au4f photoemission peaks both indicate a surface coverage θ≈0.2. In the case ofmultilayers formed by immersion in pure ethanolic solutions, the Raman experiments indicate that intralayer S\S bonds are not formed, and hence that all the S\S bonds are of the interlayer type.